TATHBIIQU ASALIIBU AL-AS`ILATI WA AL-AJWIBATI WA ATSARUHA 'ALAA TAHSHIILI TA’LIMI AL-LUGHAH AL-‘ARABIYYAH FII SHAFI AT-TSAMIN “A” FII AL-MADRASAH AT-TSANAWIYYAH BI MA’HAD UMMUL QURO AL-ISLAMI BOGOR - Muthmainnah; Lukman Taufik Akasahtia; Asriani (Program Studi Pendidikan Bahasa Arab, 2022)
The study is established with the background of the Arab teacher applying questions and answers methods to look at the students' studies in the class. This method is usually used by teachers and interned with other methods such as lecture methods, discussion methods, etc. This study aims to study and get accurate data on how the question-and-answer method is applied and how it affects student learning. The method used in this study is a quantitative descriptive method. The population in this study is class viii a princess student and used the saturated sample with a total of 47 respondents. Data collection techniques using questionnaires or angkets, documents and interviews. Processing data using a help version of the SPSS 23 application. Overall, studies show the effect of applying deductions at 36 %, a good rating of 48,02 and a perfect 77% through research. Based on analysis of the hypothetical evidence, the value t calculates less than t tables (0,637 < 2014), and thus it can be said that there is no significant effect between applying q&a methods to student study with a variable associated level of 1,3 %.